Brine formation in relation to climate changes and ice retreat during the last 15, 000 years in Storfjorden, Svalbard, 76–78°N. (6th October 2014) - Rasmussen, T. L.; Thomsen, E.
Abstract: Storfjorden, Svalbard, is an area of intense brine formation. The brine is cold, dense, rich in oxygen and CO2, and has reduced pH. Storfjorden is unique because it contains well‐preserved agglutinated foraminifera dating back to the beginning of the last deglaciation. We have investigated the distribution of calcareous and agglutinated benthic foraminifera, benthic oxygen and carbon isotopes, calcium carbonate, total organic carbon, and ice‐rafted debris in five cores from Storfjorden comprising the Holocene and the deglaciation. The purpose of the study is to reconstruct brine formation in the past under different climate scenarios. The data indicate that in Storfjorden the ratio of agglutinated to calcareous benthic foraminifera can be taken as a measure of the strength of brine formation. The foraminiferal data, which are supported by stable isotopes, degree of fragmentation, and geochemical parameters, signify that brine formation intensified during cold periods and weakened during warm periods. During the deglaciation, increased brine flow coincides with the Older Dryas, the Intra‐Allerød Cold Period, and the Younger Dryas. Brine formation increased from circa 8200 years B.P. reaching periodic maxima during the last 4000 years B.P. in response to the unstable climate. Maximum brine production correlates with the Dark Ages Cold Period circa 1500–1100 years B.P. and the Little Ice Age circa 600–100 years B.P. Lower production correlates with the Roman Warm Period circa 2500–2000 years B.P. and the Medieval Warm Period circa 1000–700 years B.P. Key Points: Brine formation is reconstructed for the deglaciation and Holocene periods Brine formation in Storfjorden, Svalbard is closely linked to climate Brines reached periodic maxima during the late Holocene (last circa 4000 years)